DINAMIKA MULTIPARTAI DALAM PENETAPAN APBD (Studi Kasus DPRD Kabupaten Tabanan dan DPRD Kabupaten Klungkung) - Priliandari, Karina Chandra; Erawan, I Ketut Putra; Jayanthi Mertha, A. A. Sagung Mirah Mahaswari (Jurnal Nawala Politika, 2019)
ABSTRACT This research have the purpose is to find out the comparison between Tabanan Regency which is dominated by a particular party and Klungkung Regency which is not dominated in the process of determining the APBD to find out how the debate during the process of determining the APBD takes place. Descriptive qualitative research methods used in this research with purposive sampling technique. The findings of this study are that Tabanan Regency is dominated by a dominant party system. This condition causes the determination of APBD in Tabanan Regency without experiencing significant obstacles and debates. Determination of APBD in Klungkung Regency is still multi-stakeholder and experiences quite a lot of debate and the dominant party system and polarized pluralism system directly affect the process of determining the APBD in Tabanan and Klungkung Regencies. Key words:APBD, Party System, Tabanan Regency, and Klungkung Regency.